ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI TH 2010-2012) - Sri Murwanti; Mulyono Mulyono (Benefit: Jurnal Manajemen dan Bisnis, 2015)
This study aims to analyze the influence of : 1 ) Return on Assets ( ROA ) to the stock price onthe banking companies listed on the Stock Exchange th period 2010-2012 ; 2 ) Return On Equity ( ROE) to the stock price on the banking companies listed on the Stock Exchange th period 2010-2012 ; 3 ) NetProfit Margin (NPM ) on stock prices in the banking companies listed on the Stock Exchange th period2010-2012 ; 4 ) Earning per share (EPS ) to the stock price on the banking companies listed on the StockExchange th period 2010-2012 ; 5 ) Price Earning Ratio ( PER ) on stock prices in the banking companieslisted on the Stock Exchange th period 2010-2012 ; and 6 ) ROA , ROE , NPM , EPS , PER simultaneously on stock prices in the banking companies listed on the Stock Exchange th period 2010-2012 . This research was conducted using secondary data . The population in this study are listed banking industry in IndonesiaStock Exchange ( IDX ) of 28 companies , the samples taken were 84 observations by purposive samplingtechnique . The method of analysis used by multiple regression analysis with first tested the classicalassumptions include normality test, multicollinearity , heteroscedasticity test , and hypothesis testing usedis a simultaneous significant test ( Test F ) , partial significant test ( the self- t ) . The results of this studyprove that : ROA no significant effect on the stock price on the banking companies listed on the StockExchange th period 2010 - 2012 , ROE no significant effect on the stock price on the banking companieslisted on the Stock Exchange th period 2010 - 2012 , NPM significantly influence stock price on the bankingcompanies listed on the Stock Exchange th period 2010 - 2012 , EPS significantly influence stock prices inthe banking company listed on the Stock Exchange th period 2010 - 2012 , PER no significant effect on thestock price on the banking companies listed on the Stock Exchange th period 2010 - 2012 , ROA , ROE ,NPM , EPS and PER simultaneously significant effect on stock prices in the banking companies listed onthe Stock Exchange th period 2010 - 2012